7x(3x-4)-5x(2x-3)-(3x)=

Simple and best practice solution for 7x(3x-4)-5x(2x-3)-(3x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x(3x-4)-5x(2x-3)-(3x)= equation:


Simplifying
7x(3x + -4) + -5x(2x + -3) + -1(3x) = 0

Reorder the terms:
7x(-4 + 3x) + -5x(2x + -3) + -1(3x) = 0
(-4 * 7x + 3x * 7x) + -5x(2x + -3) + -1(3x) = 0
(-28x + 21x2) + -5x(2x + -3) + -1(3x) = 0

Reorder the terms:
-28x + 21x2 + -5x(-3 + 2x) + -1(3x) = 0
-28x + 21x2 + (-3 * -5x + 2x * -5x) + -1(3x) = 0
-28x + 21x2 + (15x + -10x2) + -1(3x) = 0

Remove parenthesis around (3x)
-28x + 21x2 + 15x + -10x2 + -1 * 3x = 0

Multiply -1 * 3
-28x + 21x2 + 15x + -10x2 + -3x = 0

Reorder the terms:
-28x + 15x + -3x + 21x2 + -10x2 = 0

Combine like terms: -28x + 15x = -13x
-13x + -3x + 21x2 + -10x2 = 0

Combine like terms: -13x + -3x = -16x
-16x + 21x2 + -10x2 = 0

Combine like terms: 21x2 + -10x2 = 11x2
-16x + 11x2 = 0

Solving
-16x + 11x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-16 + 11x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-16 + 11x)' equal to zero and attempt to solve: Simplifying -16 + 11x = 0 Solving -16 + 11x = 0 Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 11x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 11x = 0 + 16 11x = 0 + 16 Combine like terms: 0 + 16 = 16 11x = 16 Divide each side by '11'. x = 1.454545455 Simplifying x = 1.454545455

Solution

x = {0, 1.454545455}

See similar equations:

| (4x-28)+(11x+13)=180 | | 63=6.50(p)+17.50 | | 4y-8y=-4-32 | | (4x+10)+(y-10)=80 | | -16x^2+96x-48=0 | | 5(2x-3)-3(2-x)=3(7x+1) | | a=.33L+160000 | | (x+10)+4y=80 | | 4=-2x | | 7[2-(4+6x)]-2x=-16+2(1-22x) | | X+-.40X=56000 | | x(x-10)+21=0 | | 6a^2-96=0 | | (8x^3+16x^2+32)=0 | | 12y=2 | | 8x=31 | | x+2*3/4=5/4-7+6 | | h=2f | | 3x+5y+2x-3y=0 | | 1600000=0.04X-78.56 | | 264-6x=39x+24 | | -[5z-(12z+4)]=4+(6z+1) | | 3xy+x=9 | | x^2+680=62x+8 | | 0=-16t^2+48t+160 | | 6(2x-5)-4(x-2)=14 | | 5x+17= | | 9x+52=43 | | 999+999= | | 8x-29=59 | | 138.75=(3p)(.10)(1)+(p)(.07)(1) | | 4*16= |

Equations solver categories